Team interpreting as collaboration and interdependence - Hoza, Jack. (Alexandria, VA : Registry of Interpreters for the Deaf, Inc., 2010)
Based in two studies, this book explores team interpreting and reveals the potential of team members working together on all aspects of interpreting assignments.
Includes bibliographical references (p. 206-214).
Keywords: Interpreters for the deaf